Genetic Diversity of Plant Species Mangrove Sonneratia Spp. in Central Sulawesi and Its Utilization as a Learning Media - Puspayanti, Ni Made; Suleman, Samsurizal M.; Budiarsa, I Made (Jurnal Riset Pendidikan MIPA, 2019)
The mangrove Sonneratia caseolaris that grows on land (Bora) has a different morphological form from Sonneratia alba which grows on the sea coast of Parigi and Donggala. This study aims to determine the genetic diversity of mangrove species Sonneratia spp. in Central Sulawesi and utilizing research results as a learning media in the form of a genetics practicum module. The results showed that the genetic diversity of the mangrove species Sonneratia spp. in Parigi, Donggala, and Bora showed a difference, namely that Sonneratia alba which grew in Parigi and Donggala had the same similarity index, namely 88.9%, while Sonneratia caseolaris which grew in Bora had a different similarity index, namely 71.3%. From these results, a learning media in the form of a genetics practicum guide module was made and was validated by content experts, design experts, media experts, and 10 students.